Linfoma cutâneo primário difuso de grandes células B, leg type: relato de caso - Antunes, Ana Patrícia Barbosa (2025)
Introduction: Primary cutaneous lymphomas are defined as a heterogeneous group of malignant lymphoproliferative neoplasms that affect the skin, without extracutaneous involvement at the moment of the diagnosis. Primary cutaneous diffuse large B-cell lymphoma, leg type (PCDLBL-LT) represents a subgroup of these tumours. This clinical case illustrates the difficulty of diagnosing this condition, in which the family doctor (FD) played a crucial role. Case report: A 75-year-old woman, after undergoing drainage of a liquid collection in her right ankle in a private clinic, consulted the FD due to persistent drainage, oedema, and redness after several cycles of antibiotic therapy. She was referred to urgent evaluation by general surgery, which ruled out a surgical complication. In a new consultation with her FD to assess the evolution of the lesion, it showed worsening with ulceration and hypoesthesia, raising the suspicion of the skin or soft tissue tumour. After additional diagnostic tests, such as a joint CT scan that described a “fracture involving the distal peroneal diaphysis associated with swelling of soft tissues”, the patient was referred to an urgent orthopaedics consultation and after a biopsy of the lesion, she was diagnosed with PCDLBL-LT. The patient started an R-CHOP regimen followed by radiotherapy. Comment: This case illustrates the difficulty in diagnosing a primary cutaneous lymphoma. Close follow-up of the patient during numerous consultations was essential to make the diagnosis of a neoplastic disease. Considering its rapid growth and high proliferative rate, it is important to know its clinical presentation for a precocious diagnosis and efficient treatment.